Criminal Liability of Parents for Economic Exploitation of Children - Laverda Daffa Marva Ria; Ariy Khaerudin; Femmy Silaswati Farried (LEGAL BRIEF, 2025)
The economic exploitation of children by parents reflects social inequalities and weak legal protections for vulnerable groups in Indonesia, exacerbated by poverty, low education levels, and inadequate state oversight in the informal sector. This study aims to analyze the criminal liability of parents for the economic exploitation of children based on Indonesian positive law, including the Child Protection Law and the Criminal Code (KUHP 1946 and KUHP 2023), as well as identify gaps between legal norms and their implementation. The research employs a normative juridical approach with a statutory approach, utilizing secondary legal materials such as laws, doctrines, and relevant literature, analyzed through qualitative-descriptive methods. The results indicate that regulations prohibiting the economic exploitation of children align with the principles of child protection in Indonesia's legal system, which is vertically harmonious from the Constitution to sectoral regulations, and consistent with international instruments like the CRC and ILO Conventions. However, the criminal liability of parents is strongly based on the Child Protection Law (Articles 76I and 88) and Criminal Code provisions on participation, with theories such as strict liability and vicarious liability applicable. Despite a strong normative framework, law enforcement is hindered by low legal awareness, permissive culture, and narrow interpretations of exploitation. In conclusion, although legal norms effectively criminalize exploitation by parents, practical implementation requires stricter enforcement, consistent interpretations prioritizing the best interests of the child, and social policies to address root causes, to ensure substantive child protection